Microscopic differences in void characteristics of porous asphalt mixtures and their effect on mechanical and functional performances with different compaction methods - Sun, Junfeng; Zhang, Haitao; Xie, Kai; Sun, Ao; Liu, Jiabao; Ren, Tianqi (Construction & building materials, 2024)
This research aims to assess the microscopic differences in void characteristics of porous asphalt mixtures and their effect on mechanical and functional performance when prepared using different compaction methods. Marshall compaction (MC) and Superpave Gyratory Compactor (SGC) methods were employed to prepare the specimens, and digital image processing techniques were used to analyze the differences in void size, shape and complexity of the mixtures. Through bending, fatigue, drainage and noise reduction tests, the mechanical and functional performances of the mixture specimens under two compaction methods were compared and analyzed. The results revealed that the compaction method had a substantial effect on the specimens' drainage and noise reduction performance. Moreover, the correlation results between the meso-structure and macro performances of the mixtures indicate that SGC exhibits greater responsiveness to the overall performance of the mixtures. These findings facilitate the understanding of the compaction mechanism, thereby improving the design and compaction procedures, and providing insights into the relationship between microstructure and macroscopic performance of asphalt mixtures. •The effects of compaction methods on void characteristics and macro performances.•Analyzed the microstructural differences in void characteristics during compaction.•The SGC method strongly correlates with mixture's mechanics, while MC with functionality.•Established scale correlation between compaction methods, void parameters, and mixture performances.